Classics In Chemical Neuroscience: Fluoxetine (Prozac) - Reddy, K Surendra; Ravi, Ramavath; Savitha, V. (International Journal of Psychosocial Rehabilitation, 2025)
The first significant advancement in the treatment of depression since the development of monoamine oxidase inhibitors (MAOIs) and tricyclic antidepressants (TCAs) about thirty years prior was the release of fluoxetine (Prozac). Compared to TCAs and MAOIs, it had less side effects and was the first selective serotonin reuptake inhibitor (SSRI) to be licensed by the US Food and Drug Administration. The precise method by which fluoxetine’s clinical efficacy manifests is still up for debate, but there is no denying the significance of fluoxetine and similar SSRIs to the field. The brand name Prozac has become widely known, contributing to the reduction of long-standing stigmas attached to depression and increasing public understanding of the condition. The synthesis, pharmacology, drug metabolism, side effects, and history of fluoxetine will all be covered in this review, along with its significance for depression treatment and neuroscience in general.